Treatment landscape and burden of disease in metastatic castration-resistant prostate cancer: systematic and structured literature reviews - Leaning, Darren; Kaur, Gagandeep; Morgans, Alicia K.; Ghouse, Ray; Mirante, Osvaldo; Chowdhury, Simon (Frontiers in Oncology, 2023)
Purpose Metastatic castration-resistant prostate cancer (mCRPC) is a lethal disease that imposes a major burden on patients and healthcare systems. Three structured literature reviews (treatment guidelines, treatment landscape, and human/clinical/patient burden) and one systematic literature review (economic burden) were conducted to better understand the disease burden and unmet needs for patients with late-stage mCRPC, for whom optimal treatment options are unclear. Methods Embase®, MEDLINE®, MEDLINE® In-Process, the CENTRAL database (structured and systematic reviews), and the Centre for Reviews and Dissemination database (systematic review only) were searched for English-language records from 2009 to 2021 to identify mCRPC treatment guidelines and studies related to the treatment landscape and the humanistic/economic burden of mCRPC in adult men (aged ≥18 years) of any ethnicity. Results In total, six records were included for the treatment patterns review, 14 records for humanistic burden, nine records for economic burden, three records (two studies) for efficacy, and eight records for safety. Real-world treatment patterns were broadly aligned with treatment guidelines and provided no optimal treatment sequencing beyond second line other than palliative care. Current post-docetaxel treatments in mCRPC are associated with adverse events that cause relatively high rates of treatment discontinuation or disruption. The humanistic and economic burdens associated with mCRPC are high. Conclusion The findings highlight a lack of treatment options with novel mechanisms of action and more tolerable safety profiles that satisfy a risk-to-benefit ratio aligned with patient needs and preferences for patients with late-stage mCRPC. Treatment approaches that improve survival and health-related quality of life are needed, ideally while simultaneously reducing costs and healthcare resource utilization.